Autor Tema: Determinant of matrix

0 Usuarios y 1 Visitante están viendo este tema.

18 Febrero, 2018, 07:48 am
Leído 1549 veces

jacks

  • Experto
  • Mensajes: 672
  • País: in
  • Karma: +0/-0
  • Sexo: Masculino
if \( A \) is a \( 3\times 3 \) matrix such that \( A^3=O \).Then

 \( |\frac{A^2}{2}+A+I| \) and \( |\frac{A^2}{2}-A+I| \)

18 Febrero, 2018, 10:25 am
Respuesta #1

Fernando Revilla

  • Administrador
  • Mensajes: 10,669
  • País: es
  • Karma: +0/-0
  • Sexo: Masculino
  • Las matemáticas son demasiado humanas (Brouwer).
    • Fernando Revilla
if \( A \) is a \( 3\times 3 \) matrix such that \( A^3=O \).Then \( |\frac{A^2}{2}+A+I| \) and \( |\frac{A^2}{2}-A+I| \)

One way: if \( A^3=0 \) then, the possiible minimal polynomials of \( A \) are \( \mu_i(\lambda)=\lambda^i \), \( i=1,2,3 \) with respective canonical Jordan forms

          \( J_1=\begin{bmatrix}{0}&{}&{}\\{}&{0}&{}\\{}&{}&{0}\end{bmatrix},\quad J_2=\begin{bmatrix}{0}&{1}&{}\\{0}&{0}&{}\\{}&{}&{0}\end{bmatrix},\quad J_3=\begin{bmatrix}{0}&{0}&{1}\\{0}&{0}&{0}\\{0}&{0}&{0}\end{bmatrix}. \)

Then, there exists \( P \) invertible matrix such that \( A=PJ_iP^{-1} \) so,

          \( \frac{1}{2}A^2+A+I=P\left(\frac{1}{2}J_i^2+J_i+I\right)P^{-1} \)
          \( \frac{1}{2}A^2-A+I=P\left(\frac{1}{2}J_i^2-J_i+I\right)P^{-1} \)

But for all \( i=1,2,3 \) we have

          \( \frac{1}{2}J_i^2+J_i+I=\begin{bmatrix}{1}&{*}&{*}\\{0}&{1}&{*}\\{0}&{0}&{1}\end{bmatrix},\quad \frac{1}{2}J_i^2-J_i+I=\begin{bmatrix}{1}&{*}&{*}\\{0}&{1}&{*}\\{0}&{0}&{1}\end{bmatrix}. \)

As similar matrices have the same determinant,

         \( \left | \frac{1}{2}A^2+A+I \right |=\left |{\frac{1}{2}J_i^2+J_i+I}\right |=1,\quad \left | \frac{1}{2}A^2-A+I \right |=\left |{\frac{1}{2}J_i^2-J_i+I}\right |=1. \)

   

18 Febrero, 2018, 10:32 am
Respuesta #2

jacks

  • Experto
  • Mensajes: 672
  • País: in
  • Karma: +0/-0
  • Sexo: Masculino
Thanks fernado  revilla for nice solution. Can be solve it without  without jordon form.

Please explain

18 Febrero, 2018, 12:08 pm
Respuesta #3

Fernando Revilla

  • Administrador
  • Mensajes: 10,669
  • País: es
  • Karma: +0/-0
  • Sexo: Masculino
  • Las matemáticas son demasiado humanas (Brouwer).
    • Fernando Revilla
Thanks fernado  revilla for nice solution. Can be solve it without  without jordon form.

if \( A \) is a \( 3\times 3 \) matrix such that \( A^3=O \).Then \( |\frac{A^2}{2}+A+I| \) and \( |\frac{A^2}{2}-A+I| \)

Really, what does the problem ask? Need you find both determinants? Or only a relation between them. For instance, as \( A^4=0 \) then \( \left(\frac{1}{2}A^2+A+I\right)\left(\frac{1}{2}A^2-A+I\right)=\ldots=\frac{1}{4}A^4+I=I \) so, \( \left(\frac{1}{2}A^2+A+I\right)^{-1}=\frac{1}{2}A^2-A+I \) and \( \left|\frac{A^2}{2}+A+I\right|=\left|\frac{A^2}{2}-A+I\right|^{-1} \).
   

18 Febrero, 2018, 01:03 pm
Respuesta #4

jacks

  • Experto
  • Mensajes: 672
  • País: in
  • Karma: +0/-0
  • Sexo: Masculino
Actually Problem asked for value of both determinants.

18 Febrero, 2018, 06:03 pm
Respuesta #5

Fernando Revilla

  • Administrador
  • Mensajes: 10,669
  • País: es
  • Karma: +0/-0
  • Sexo: Masculino
  • Las matemáticas son demasiado humanas (Brouwer).
    • Fernando Revilla
Actually Problem asked for value of both determinants.

Well, so far I can't find those values without using Jordan forms.

P.S. But possibly, tomorrow will be another day.  :)

19 Febrero, 2018, 03:25 am
Respuesta #6

jacks

  • Experto
  • Mensajes: 672
  • País: in
  • Karma: +0/-0
  • Sexo: Masculino
Thanks fernedo revilla.

19 Febrero, 2018, 05:08 am
Respuesta #7

Masacroso

  • Héroe
  • Mensajes: 2,047
  • País: es
  • Karma: +4/-0
Observe that \( \displaystyle e^A:=I+A+\frac{A^2}2 \). Thus \( \det(A^2/2+A+I)=\det(e^A)=e^{\operatorname{tr}(A)}=e^0=1 \). The other case is almost identical, just replace \( A \) by \( -A \) in the exponential.

19 Febrero, 2018, 07:50 am
Respuesta #8

jacks

  • Experto
  • Mensajes: 672
  • País: in
  • Karma: +0/-0
  • Sexo: Masculino
To masacroso how we write \( e^x=1+x+\frac{x^2}{2} \) because it is \( e^x=\sum^{\infty}_{n=0}\frac{x^n}{n!} \).Thanks

19 Febrero, 2018, 07:58 am
Respuesta #9

Fernando Revilla

  • Administrador
  • Mensajes: 10,669
  • País: es
  • Karma: +0/-0
  • Sexo: Masculino
  • Las matemáticas son demasiado humanas (Brouwer).
    • Fernando Revilla
To masacroso how we write \( e^x=1+x+\frac{x^2}{2} \) because it is \( e^x=\sum^{\infty}_{n=0}\frac{x^n}{n!} \).Thanks

If \( A^3=0 \) then, \( A^4=A^5=\ldots =0 \) so, \( e^A=\sum^{\infty}_{n=0}\frac{A^n}{n!}=I+A+\frac{1}{2}A^2 \).

19 Febrero, 2018, 08:50 am
Respuesta #10

Fernando Revilla

  • Administrador
  • Mensajes: 10,669
  • País: es
  • Karma: +0/-0
  • Sexo: Masculino
  • Las matemáticas son demasiado humanas (Brouwer).
    • Fernando Revilla
Observe that \( \displaystyle e^A:=I+A+\frac{A^2}2 \). Thus \( \det(A^2/2+A+I)=\det(e^A)=e^{\operatorname{tr}(A)}=e^0=1 \). The other case is almost identical, just replace \( A \) by \( -A \) in the exponential.

An elegant solution. Now the question for Jacks is: What topics are covered in those olympiad problems? Can we use, for example the exponential matrix concept?

19 Febrero, 2018, 11:18 am
Respuesta #11

Luis Fuentes

  • el_manco
  • Administrador
  • Mensajes: 46,537
  • País: es
  • Karma: +0/-0
  • Sexo: Masculino
Hi

 Another way. Take:

\(  f(t)=det\left(\dfrac{(At)^2}{2}+(At)+Id\right) \)

 Note that \( f(t) \) is a polynomial. Using that \( A^3=0 \) check that:

\(  f(t)^2=det(2(At)^2+2(At)+Id)=f(2t) \)

But:

\(  deg(f(t))=deg(f(2t))=deg(f(t)^2)=2deg(f(t)) \)

 so \( deg(f(t))=0 \), that is, \( f(t) \) is constant:

\( f(1)=f(-1)=f(0)=det(Id)=1 \).

Best regards.

19 Febrero, 2018, 11:45 am
Respuesta #12

Fernando Revilla

  • Administrador
  • Mensajes: 10,669
  • País: es
  • Karma: +0/-0
  • Sexo: Masculino
  • Las matemáticas son demasiado humanas (Brouwer).
    • Fernando Revilla
Another way. Take: \(  f(t)=det\left(\dfrac{(At)^2}{2}+(At)+Id\right) \) ....

Good, surely that is a convenient method for an olympiad problem. All the properties used are usually covered in the corresponding syllabus.

19 Febrero, 2018, 01:08 pm
Respuesta #13

Abdulai

  • Moderador Global
  • Mensajes: 2,342
  • País: ar
  • Karma: +0/-0
  • Sexo: Masculino

Siendo  \( A^3=0\;\;\longrightarrow\;\; \left(I+\frac{1}{2}A\right)\left(I-\frac{1}{2}A\right)^{-1}=I+A+\frac{1}{2}A^2 \)

fácil de demostrar expandiendo   \( \left(I+\frac{1}{2}A\right)  = \left(I+A+\frac{1}{2}A^2\right)\left(I-\frac{1}{2}A\right) \)

\( \therefore\quad \text{det}\left(I+A+\frac{1}{2}A^2\right)= \dfrac{\text{det}\left(I+\frac{1}{2}A\right)}{\text{det}\left(I-\frac{1}{2}A\right)} \)

Una conocida propiedad de las matrices nilpotentes es que  \( \text{det}\left(I+N\right) = 1\quad ,\quad N \) nilpotente.

Por lo tanto  \( \text{det}\left(I+A+\frac{1}{2}A^2\right)= \dfrac{1}{1} \)


Lo mismo para el otro caso  \( \text{det}\left(I-A+\frac{1}{2}A^2\right)= \dfrac{\text{det}\left(I-\frac{1}{2}A\right)}{\text{det}\left(I+\frac{1}{2}A\right)}=1 \)



19 Febrero, 2018, 02:58 pm
Respuesta #14

Masacroso

  • Héroe
  • Mensajes: 2,047
  • País: es
  • Karma: +4/-0
Other way, more elementary in my opinion: because they are polynomials it is enough to decompose the polynomials in it factors and, due to the fact that the determinant is a multiplicative function, then we can achieve the same result, that is

\( \displaystyle \det(A^2/2+A+I)=\frac1{2^3}\det(A^2+2A+2I)=\frac1{8}\det((A-\lambda I)(A-\bar\lambda I))=\frac18\det(A-\lambda I)\det(A-\bar\lambda I)=\frac18\lambda^3\bar\lambda^3=\frac{|\lambda|^6}8=1 \)

for \( \lambda \) and \( \bar\lambda \) the two roots of the polynomial \( x^2+2x+2 \), that is \( \lambda=-1+i \) and \( \bar\lambda =-1-i \), then clearly \( |\lambda|^2=\lambda\cdot\bar\lambda=2 \) and the result follows.

The important step is to note that \( \det(A-\lambda I)=-\lambda ^3 \) because a nilpotent matrix can be transformed, under a change of basis, in an upper-triangular matrix where the diagonal is full of zeros. A change of basis doesnt change the value of the determinant so we can see \( A \) in the form that we please.

19 Febrero, 2018, 04:58 pm
Respuesta #15

Luis Fuentes

  • el_manco
  • Administrador
  • Mensajes: 46,537
  • País: es
  • Karma: +0/-0
  • Sexo: Masculino
Hola

The important step is notice that \( \det(A-\lambda I)=-\lambda ^3 \) because a nilpotent matrix can be transformed, under a change of basis, in an upper-triangular matrix where the diagonal is full of zeros. A change of basis doesnt change the value of the determinant so we can see \( A \) in the form that we please.

Here we are using a "Jordan matrix/upper triangular matrix" type argument again.

The result \( A \) nilpotent implies \( det(A+I)=1 \) can be proved again playing with the polynomial \( f(t)=det(At+I) \) and its powers \( f(t)^n \).   ;D

Best regards.

26 Febrero, 2018, 12:59 pm
Respuesta #16

jacks

  • Experto
  • Mensajes: 672
  • País: in
  • Karma: +0/-0
  • Sexo: Masculino
Thanks Moderator, Admin, Masacraso got